One minute excellence: the pathway to breakthrough customer service, a review - Duve, Richard (Midlands State University, 2015)
The paper discusses the key strategies to breakthrough customer service. The paper also endeavors to highlight, first that the only way to “wow” the customers and have a durable relationship is through one minute excellence. A 21st Century philosophy which postulates that in this era of maintaining symbiotic type of relationships with customers, we need personal “WOW” , to abandon the old paradigm of treating customers as second class citizens, to customer “WOW” which results in customer focused culture. The paper further discusses service experiences by marketing practitioners including personal excellence experiences by the researcher right in the delight arenas.